Understanding Sitatunga (Tragelaphus Spekii) Habitats Through Diet Analysis In Rushebeya-Kanyabaha Wetland, Uganda - Ndawula, Joseph; Tweheyo, Mnason; Tumusiime, David M.; Eilu, Gerald (African Journal of Ecology, 2011)
Between January and December 2008, we assessed the diet and habitat selection of sitatunga, a highly endangered tropical wetland antelope threatened by habitat loss in Rushebeya-Kanyabaha wetland. Microhistological faecal analysis and vegetative sampling methods were used to assess plant forms, species and seasonal changes in the sitatunga diet. Habitat use was indirectly determined by assessing feeding patterns, distribution of dung and trails within the wetland. Sitatunga fed mainly on herbs, sedges, grasses and shrubs. A total of 34 plant species were recorded as eaten by sitatunga. The most eaten plant species was Cyperus papyrus L. (22%). Malenthera scandens Schum. & Thonn., Polygonum senegalense Meisu (12%) and Polygonum pulchrum Blume (5%) were the most eaten herbs. Zea mays L. was the most eaten agricultural crop (58% of domestic crops), mainly during the wet season. Sitatunga feeding was mainly concentrated on the wetland edge habitat (46%) where most of its food (53%) was located. The other preferred habitat was the tall closed papyrus. We conclude that the long-term survival of sitatunga requires a management plan focussing on the conservation of the most preferred plant species and habitats.
Keywords: microhistological, Rushebeya-Kanyabaha, Tragelaphus spekei, tropical wetland